Analisis Penataan Desa di Kabupaten Ogan Komering Ulu (Studi tentang Pembentukan dan Perubahan Status Desa) - Lestari, Aprilia; Bela, Herwin Sagita (UNIVERSITAS INDO GLOBAL MANDIRI)
AbstractThe establishment of villages and changes in village status not only talk about government administrative requirements, bu talso full of the interests of certain elites. The expansion of villages is made as an event to distribute power and authority by certain elites. Changing the status of the village to become sub district too. This condition cannot be separated from the village budget program provided by the government to develop villages and empower village communities.After the implementation of Law No. 6 of 2014 concerning villages followed by the Village budget Program, the structuring of villages in Ogan Komering Ulu District became the local government's concern. The village budget program has become a stimulus for certain elite wishes to try to established new villages / village expansion.However, the central government did not approve more so it did not submit proposals for villages expansion/ establish new village.This is because establish new villages / villages expansion is considered to affect the amount of budget received by the village, because the amount of village budget is based on the consideration of population and area.This condition triggered conflict between the village government and the élite who wanted to establish a new village.The conflict was the passivity of the community towards administer the village government. In addition, local governments also study deeply if there is a desire to establish new villages so that it is not used as an event for power sharing and in order to minimize the misuse of the goals of village division. For the change of village status to sub district, there has not been any significant progress from a number of villages that have changed their status in the past decade.Keywords : stucturing, formation, village changeAbstrakPembentukan desa dan perubahan status desa bukan hanya berbicara tentang persyaratan administrasi pemerintahan, tetapi juga sarat akan kepentingan elite tertentu. Pemekaran desa dijadikan sebagai ajang pembagian kekuasaan dan kewenangan oleh elite tertentu. Perubahan status desa menjadi kelurahan pun demikian. Kondisi ini tidak dapat dilepaskan dari program dana desa yang diberikan pemerintah guna membangun desa dan memberdayakan masyarakat desa. Pasca implementasi Undang-Undang Nomor 06 tahun 2014 tentang Desa yang diikuti dengan adanya program dana desa, penatan desa di kabupaten Ogan Komering Ulu menjadi perhatian pemerintah daerah. Program dana desa telah menjadi stimulus bagi keinginan elite tertentu untuk berusaha membentuk desa baru/memekarkan desa. Akan tetapi, pemerintah desa induk, lebih banyak tidak menyetujui sehingga tidak mengajukan usulan pemekaran desa/pembentukan desa baru. Hal ini dikarenakan pembentukan desa baru/pemekaran desa dianggap akan mempengaruhi jumlah dana yang diterima desa saat ini, karena jumlah dana didasarkan pada pertimbangan jumlah penduduk dan luas wilayah. Kondisi ini memicu konflik antara pemerintah desa dengan elite yang menginginkan pembentukan desa baru, konflik berupa adanya sikap ketidakpedulian dari masyarakat terhadap penyelenggaraan pemerintahan desa. Selain itu, pemerintah daerah juga mempelajari secara mendalam jika ada keinginan untuk pembentukan desa baru agar pembentukan desa baru tidak dijadikan sebagai ajang bagi-bagi kekuasaan dan guna meminimalisir penyelewangan tujuan pemekaran desa. Untuk perubahan status desa menjadi kelurahan, belum terdapat kemajuan yang signifikan dari beberapa desa yang telah berubah status dalam satu dasawarsa terakhir.Kata kunci : penataan, pembentukan, perubahan desa